Species diversity of Hyalinobatrachium glassfrogs (Amphibia: Centrolenidae) from the Guiana Shield, with the description of two new species - Castroviejo-Fisher, Santiago; Vilà, Carles; Ayarzagüena, José; Blanc, Michel; Ernst, Raffael (Zootaxa, 2011)
Basic information about the taxonomy, biology and distribution of Hyalinobatrachium glassfrogs of the Guiana Shield (GS) is scarce, ambiguous, and in many cases even contradictory. In this review we aim to clarify the current taxonomic status of this group by means of phenotypic (morphology, morphometrics and bioacoustics) and molecular (mitochondrial DNA sequences) comparisons. Eight species have previously been recognized for the GS: H. crurifasciatum, H. eccentricum, H. fleischmanni (initially described as Hylella cappellei in the GS), H. iaspidiense (with the putative synonym H. nouraguense), H. ignioculus, H. mesai, H. mondolfii, and H. taylori. Our data support the resurrection of H . cappellei from its synonymy with H. fleischmanni. Hyalinobatrachium crurifasciatum, H. eccentricum, and H. ignioculus are proposed as junior synonyms of H. cappellei. We show that none of the four paratypes of H. taylori belong to this species and we assign two to H. cappellei and two to H. mondolfii. Additional specimens previously identified as H. taylori are reassigned to H. cappellei, and hence H. taylori is redefined. Hyalinobatrachium nouraguense is confirmed as a junior syn-onym of H. iaspidiense. We also describe two new species of Hyalinobatrachium from French Guiana: Hyalinobatrachium kawense sp. nov. and Hyalinobatrachium tricolor sp. nov. In addition, and in concordance with the new taxonomic rearrangements, we provide diagnostic characters for all species, known distributions and main sources of references for their biology. We also report new distribution records for H. iaspidiense and H. mondolfii, and describe the formerly unknown tadpole of the later. Consequently, we recognize seven species of Hyalinobatrachium for the Guiana Shield: H. cappellei, H. iaspidiense, H. kawense sp. nov., H. mesai, H. mondolfii, H. taylori, and H. tricolor sp. nov. We discuss the suitability of integrative taxonomy as an approach to identify taxonomic uncertainty and consider its significance for conservation purposes. We also address the implications of our results to understand phylogeographic patterns in this area.